Validity and Reliability of the Arabic Version of the Psychosocial Impact of Dental Aesthetics Questionnaire for Yemeni Adolescents - Amal A. M. Alsanabani; Zamros Y. M. Yusof; Wan Nurazreena Wan Hassan; Khalid Aldhorae; Helmi A. Alyamani (MDPI AG, 2021)
(1) Objectives: This paper aimed to cross-culturally adapt the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) into an Arabic language version (PIDAQ(A)) for measuring the oral health related quality of life related to dental aesthetics among 12-17-year-old Yemeni adolescents. (2) Material and methods: The study comprised three parts, which were linguistic validation and qualitative interview, comprehensibility assessment, and psychometric validations. Psychometric properties were examined for validity (exploratory factor analysis (EFA), partial confirmatory factor analysis (PCFA), construct, criterion, and discriminant validity) and reliability (internal consistency and reproducibility). (3) Results: The PIDAQ(A) contained a new item. EFA extracted three factors (item factor loading 0.375 to 0.918) comprising dental self-confidence, aesthetic concern, and psychosocial impact subscales. PCFA showed good fit statistics (comparative fit index (CFI) = 0.928, root-mean-square error of approximation (RMSEA) = 0.071). In addition, invariance across age groups was tested. Cronbach's α values ranged from 0.90 to 0.93 (intraclass correlations = 0.89-0.96). A criterion validity test showed that the PIDAQ(A) had a significant association with oral impacts on daily performance scores. A construct validity test showed significant associations between PIDAQ(A) subscales and self-perceived dental appearance and self-perceived need for orthodontic braces (p < 0.05). Discriminant validity presented significant differences in the mean PIDAQ(A) scores between subjects having severe malocclusion and those with slight malocclusion. No floor or ceiling effects were detected.